2020
DOI: 10.1186/s12940-020-00649-z
|View full text |Cite
|
Sign up to set email alerts
|

Greenness, civil environment, and pregnancy outcomes: perspectives with a systematic review and meta-analysis

Abstract: Background: Various maternal conditions, especially in utero conditions and prenatal exposure to environments with air pollution and greenness, have been reviewed to address the enhancement and prevention of susceptibility to health risks, including low birthweight, preterm delivery, and preeclampsia. This study aimed to qualitatively and quantitatively investigate the associations between pregnancy outcomes and the characteristics of surrounding living environment, including greenness, air pollution, and civi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Postpartum distress was examined [ 39 ], but the effects on antenatal depression or neonatal outcomes were not investigated. This is an important topic, as the greenness of the environment was associated with reduced risks of low birth weight and preterm delivery [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum distress was examined [ 39 ], but the effects on antenatal depression or neonatal outcomes were not investigated. This is an important topic, as the greenness of the environment was associated with reduced risks of low birth weight and preterm delivery [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, between 2014 and 2020, there have been seven published systematic reviews and meta-analyses on maternal greenness exposure and birth weight alone. 8 , 13 , 14 , 15 , 16 , 17 Such rapid updates make keeping up with the systematic reviews difficult for researchers, healthcare practitioners, and policy makers. In addition, many of the systematic reviews and meta-analyses focus on a single disease or one kind of similar health endpoints.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Although some studies have reported a protective effect of greenness on birth weight, conclusions for the associations between greenness and PTB were inconsistent. 15 , 16 , 17 , 18 , 19 Some investigators have attempted to determine the association between greenness and PTB. 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Most of the studies found no associations between greenness and PTB 15 , 16 , 17 , 18 , 19 and a few studies indicated an inverse association.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 , 17 , 18 , 19 Some investigators have attempted to determine the association between greenness and PTB. 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Most of the studies found no associations between greenness and PTB 15 , 16 , 17 , 18 , 19 and a few studies indicated an inverse association. 26 , 27 Currently, it remains unclear how greenness may benefit human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation